A Critical Review on Varied Aspects of Gestational Diabetes Mellitus (GDM) and It’s Associations with Placenta - Arkaprava Mukhopadhyay; Bishal K. Dey; Subhankar Chowdhury; Subhajit Maity (Indian Journal of Endocrinology and Metabolism)
Gestational diabetes mellitus (GDM) is defined as first onset hyperglycemic state during pregnancy. It is a common complication of pregnancy, caused by a combination of genetic and environmental factors. The pathophysiology of GDM is not yet fully understood. Placenta is an organ developed in gestational period and acts as a bridge between fetal and maternal body. Placenta has various roles like exchanging metabolites, nutrients, O2-CO2 transport, waste removal etc., during gestation - all of which are important for maintaining a healthy pregnancy. Placenta also acts as an endocrine organ, releasing different hormones like placental lactogen and placental growth hormone. These hormones are known to contribute to pathogenesis of GDM. There can be other genetic changes in the placenta, that can further our understanding of GDM. This review attempts to summarise the possible association of genes with GDM and their contribution to placental dysfunction, as reported in recent times.